Do we adequately diagnose early gastric cancer in Turkey - Hüsnü Oğuz KOÇ; Yavuz Selim SARI; Hasan BEKTAŞ; Vahit TUNALI; Orhan ŞAHİN and Kerim ÖZAKAY and Ersöz FEYZULLAH (Turkish Journal of Gastroenterology, 2019)
-